2020
DOI: 10.1038/s41564-020-00798-4
|View full text |Cite
|
Sign up to set email alerts
|

β-Barrel proteins tether the outer membrane in many Gram-negative bacteria

Abstract: Gram-negative bacteria have a cell envelope that comprises an outer membrane (OM), a peptidoglycan (PG) layer and an inner membrane (IM) 1 . The OM and PG are load-bearing, selectively permeable structures that are stabilized by cooperative interactions between IM and OM proteins 2 , 3 . In E. coli , Braun’s lipoprotein (Lpp) forms the only covalent tether between the OM and PG and is crucial for cell envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…Some of the DpaA homologues might function as LD-carboxypeptidase, consistent with their classification in the MEROPS peptidase database (39) within the C82.A01 peptidase subfamily along with the LD-carboxypeptidases Csd6 from Helicobacter pylori and Pgp2 from Campylobacter jejuni (40, 41). Alternatively, or in addition, DpaA could detach different substrates from PG, for example OMPs in α- and γ-proteobacteria (24, 25). Indeed, a search within the genomes of α- and γ-proteobacteria with PG-attached OMPs identified genes encoding DpaA-like proteins in all of them ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the DpaA homologues might function as LD-carboxypeptidase, consistent with their classification in the MEROPS peptidase database (39) within the C82.A01 peptidase subfamily along with the LD-carboxypeptidases Csd6 from Helicobacter pylori and Pgp2 from Campylobacter jejuni (40, 41). Alternatively, or in addition, DpaA could detach different substrates from PG, for example OMPs in α- and γ-proteobacteria (24, 25). Indeed, a search within the genomes of α- and γ-proteobacteria with PG-attached OMPs identified genes encoding DpaA-like proteins in all of them ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, at present we cannot exclude the possibility that some bacteria employ DpaA-like enzymes to remove non-canonical D-amino acids, which are toxic when incorporated at a high amount (47). The recent discovery of PG-attached OMPs in certain α-proteobacteria suggests that the DpaA-like enzymes in these species function to detach OMPs from PG (24, 25). In support of this hypothesis, the attachment of OMPs to PG occurs via N-terminal glycine or alanine, and the attachment of OM-lipoprotein LimB via an internal lysine residue, producing the very same amide bonds as in TetraGly4 or in PG-bound Lpp in E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While another PGattached lipoprotein has been described for Pseudomonas spp., the covalent attachment of PG to OM-localized proteins has not been studied in depth for PG of other diderm bacteria (23). This changed recently when two publications reported the covalent attachment of certain OM b-barrel proteins (OMPs) in a wide range of Alphaproteobacteria (24,25). Additionally to OMPs, one of the studies identified the OM-anchored lipoprotein LimB attached to PG in Coxiella burnetii (25).…”
mentioning
confidence: 99%